Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
To solve the equation [tex]\(\frac{2x - 1}{y} = \frac{w + 2}{2z}\)[/tex] for [tex]\(w\)[/tex], follow these steps:
1. Start with the initial equation:
[tex]\[ \frac{2x - 1}{y} = \frac{w + 2}{2z} \][/tex]
2. Cross-multiply to eliminate the fractions:
[tex]\[ (2x - 1) \cdot 2z = (w + 2) \cdot y \][/tex]
3. Distribute the terms on each side:
[tex]\[ 2z \cdot (2x - 1) = y \cdot (w + 2) \][/tex]
This simplifies to:
[tex]\[ 4xz - 2z = wy + 2y \][/tex]
4. Isolate the term with [tex]\(w\)[/tex]:
[tex]\[ 4xz - 2z - 2y = wy \][/tex]
5. Subtract [tex]\(2y\)[/tex] on both sides to isolate [tex]\(wy\)[/tex]:
[tex]\[ 4xz - 2z = wy + 2y \quad \Rightarrow \quad 4xz - 2z - 2y = wy \][/tex]
6. Divide both sides by [tex]\(y\)[/tex] to solve for [tex]\(w\)[/tex]:
[tex]\[ w = \frac{4xz - 2z}{y} - 2 \][/tex]
Hence, the solution for [tex]\(w\)[/tex] in terms of [tex]\(x\)[/tex], [tex]\(y\)[/tex], and [tex]\(z\)[/tex] is:
[tex]\[ w = \frac{4xz - 2z}{y} \][/tex]
And this is the final simplified form of [tex]\(w\)[/tex].
1. Start with the initial equation:
[tex]\[ \frac{2x - 1}{y} = \frac{w + 2}{2z} \][/tex]
2. Cross-multiply to eliminate the fractions:
[tex]\[ (2x - 1) \cdot 2z = (w + 2) \cdot y \][/tex]
3. Distribute the terms on each side:
[tex]\[ 2z \cdot (2x - 1) = y \cdot (w + 2) \][/tex]
This simplifies to:
[tex]\[ 4xz - 2z = wy + 2y \][/tex]
4. Isolate the term with [tex]\(w\)[/tex]:
[tex]\[ 4xz - 2z - 2y = wy \][/tex]
5. Subtract [tex]\(2y\)[/tex] on both sides to isolate [tex]\(wy\)[/tex]:
[tex]\[ 4xz - 2z = wy + 2y \quad \Rightarrow \quad 4xz - 2z - 2y = wy \][/tex]
6. Divide both sides by [tex]\(y\)[/tex] to solve for [tex]\(w\)[/tex]:
[tex]\[ w = \frac{4xz - 2z}{y} - 2 \][/tex]
Hence, the solution for [tex]\(w\)[/tex] in terms of [tex]\(x\)[/tex], [tex]\(y\)[/tex], and [tex]\(z\)[/tex] is:
[tex]\[ w = \frac{4xz - 2z}{y} \][/tex]
And this is the final simplified form of [tex]\(w\)[/tex].
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.